Gestational diabetes in women living with HIV in Botswana: lower rates with dolutegravir‐ than with efavirenz‐based antiretroviral therapy. Issue 8 (18th May 2021) - Mmasa, KN; Powis, K; Sun, S; Makhema, J; Mmalane, M; Kgole, S; Masasa, G; Moyo, S; Gerschenson, M; Mohammed, T; Legbedze, J; Abrams, EJ; et al.
Abstract : Background: There are few data on the prevalence of gestational diabetes (GDM) in pregnant women living with HIV (WLHIV) in sub‐Saharan Africa, particularly those using integrase strand transfer inhibitors such as dolutegravir (DTG). Methods: We prospectively enrolled pregnant WLHIV and pregnant women without HIV ≥18 years old in Gaborone, Botswana, excluding those with pre‐existing diabetes. We screened for GDM using a 75 g oral glucose tolerance test (OGTT) performed at 24–28 weeks' gestation or at the earliest prenatal visit for those presenting after 28 weeks. Logistic regression models were fitted to assess the association between maternal HIV infection and GDM. Subgroup analyses were performed among WLHIV to assess the association between maternal antiretroviral therapy (ART) in pregnancy [DTG vs . efavirenz (EFV) with tenofovir/emtricitabine] and GDM. Results: Of 486 pregnant women, 66.5% were WLHIV, and they were older than women without HIV (median age 30 vs . 25 years, P  < 0.01). Among WLHIV, 97.8% had an HIV‐1 RNA level < 400 copies/mL at enrolment. Overall, 8.4% had GDM with similar rates between WLHIV and those without HIV (9.0% vs . 7.4%). The WLHIV receiving DTG‐based ART had a 60% lower risk for GDM compared with those on EFV‐based ART (adjusted odds ratio = 0.40, 95% CI: 0.18–0.92) after adjusting for confounders. Conclusions: Pregnant WLHIV on ART in Botswana were not at increased risk of GDM compared with women without HIV. Among WLHIV, the risk of GDM was lower with DTG‐ than with EFV‐based ART. Further studies with larger cohorts are warranted to confirm these findings.